Into the depths: Techniques for in vitro three-dimensional microtissue visualization. (November 2015) - Kabadi, Pranita K.; Vantangoli, Marguerite M.; Rodd, April L.; Leary, Elizabeth; Madnick, Samantha J.; Morgan, Jeffrey R.; Kane, Agnes; Boekelheide, Kim
Three-dimensional (3-D) in vitro platforms have been shown to closely recapitulate human physiology when compared with conventional two-dimensional (2-D) in vitro or in vivo animal model systems. This confers a substantial advantage in evaluating disease mechanisms, pharmaceutical drug discovery, and toxicity testing. Despite the benefits of 3-D cell culture, limitations in visualization and imaging of 3-D microtissues present significant challenges. Here we optimized histology and microscopy techniques to overcome the constraints of 3-D imaging. For morphological assessment of 3-D microtissues of several cell types, different time points, and different sizes, a two-step glycol methacrylate embedding protocol for evaluating 3-D microtissues produced using agarose hydrogels improved resolution of nuclear and cellular histopathology characteristic of cell death and proliferation. Additional immunohistochemistry, immunofluorescence, and in situ immunostaining techniques were successfully adapted to these microtissues and enhanced by optical clearing. Utilizing the Clear T2 protocol greatly increased fluorescence signal intensity, imaging depth, and clarity, allowing for more complete confocal fluorescence microscopy imaging of these 3-D microtissues compared with uncleared samples. The refined techniques presented here address the key challenges associated with 3-D imaging, providing new and alternative methods in evaluating disease pathogenesis, delineating toxicity pathways, and enhancing the versatility of 3-D in vitro testing systems in pharmacological and toxicological applications.